THE EFFECT OF QUALITY OF WORK LIFE ON TEACHER JOB SATISFACTION - Hamidi, Hamidi; Jufri, A Wahab; Karta, Wayan (Erudio Journal of Educational Innovation, 2019)
The purpose of this study was to determine the effect of work life quality on job satisfaction of teachers of senior high school in Mataram city. This research is a quantitative research with ex-post facto method. The population of this study was all teachers of senior high school in Mataram city, which amounted to 580. The study samples were 85 teachers taken using the proportionate random sampling technique. The results of the study are: 1) there is an influence of the quality of work life by 9.2% on the job satisfaction of senior high school teachers in Mataram city. Thus, it can be concluded that the better the quality of work life of senior high school teachers' job satisfaction in Mataram city will increase.Keywords: Quality of Work Life; Teacher Job Satisfaction